2011
DOI: 10.1093/nar/gkr089
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of single-stranded phosphorothioate modified antisense oligonucleotide accumulation in hepatocytes

Abstract: Single-stranded antisense oligonucleotides (SSOs) are used to modulate the expression of genes in animal models and are being investigated as potential therapeutics. To better understand why synthetic SSOs accumulate in the same intracellular location as the target RNA, we have isolated a novel mouse hepatocellular SV40 large T-antigen carcinoma cell line, MHT that maintains the ability to efficiently take up SSOs over several years in culture. Sequence-specific antisense effects are demonstrated at low nanomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
269
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(290 citation statements)
references
References 41 publications
18
269
1
1
Order By: Relevance
“…These results indicate that functional uptake by cells in culture does not appear to be mediated by clathrin-, caveolae-or lipid raft-dependent pathways. Similarly to our studies, Koller et al (14) reported that functional uptake of a single-stranded phosphorothioate modified antisense oligonucleotide is not mediated by clathrin or caveolin.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…These results indicate that functional uptake by cells in culture does not appear to be mediated by clathrin-, caveolae-or lipid raft-dependent pathways. Similarly to our studies, Koller et al (14) reported that functional uptake of a single-stranded phosphorothioate modified antisense oligonucleotide is not mediated by clathrin or caveolin.…”
supporting
confidence: 90%
“…The present study suggested that functional uptake of sgRNA is an intracellular vesicular uptake process, since it is blocked by choroquine and brefeldin A. Recently, it has been reported that inhibition of the adaptor protein AP2M1 with small interfering RNA attenuated the antisense effects in cultured hepatocytes (14,24). Additional studies are required to determine whether AP2M1 mediates the effects of naked sgRNAs and to fully identify methods of sgRNA uptake.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…A series of uniform chimeric 20-mer phosphorothioate oligonucleotides containing 2'-O -methoxyethyl groups at positions 1-5 and 15-20 targeted to murine apoB, MTP, and a control ASO were synthesized and purifi ed on an automated DNA synthesizer using phosphoramidite chemistry as previously described (13). The sequences evaluated were as follows: apoB ASO-ISIS 147764 (5 ′ -GTCCC TGAAGATGTC AATGC -3 ′ ), MTP ASO-ISIS 144477 (5 ′ -CCCAG CACCTGGTTT GCCGT -3 ′ ), and one of two control ASOs-ASO 1 (5 ′ -AGCAT AGTTAACGAG CTCCC -3 ′ ) or ASO 2 (5 ′ -AGCAT AGTTAACGAG CTCCC -3 ′ ), with underlining indicating 2'-O -methoxyethyl-modifi ed bases.…”
Section: Antisense Oligonucleotidesmentioning
confidence: 99%
“…29,36 The precise mechanisms and molecular events resulting in ASO endocytotic uptake are only partially understood and are an intense area of research. 36 Nonetheless, the nucleic acid-based therapeutics has been extensively characterized in numerous biological systems, and it is now understood that, on systemic delivery, unformulated ASOs rapidly distribute to most tissues, and once taken up by cells, these stabilized molecules have prolonged tissue halflives of up to 2 weeks in rodents and in man. 29 The improvement in potency and ADME properties for second-generation ASOs in vivo over the firstgeneration chemistry has been shown to be as much as 10-fold, and, fortuitously, MOE Gapmers also benefit from a significantly reduced proinflammatory capacity, resulting in improved safety properties and a significantly increased therapeutic window (see Figure 2).…”
Section: Rna Therapeutics Based On Antisense Principlesmentioning
confidence: 99%